Le vocatif en -'ī' de la deuxième déclinaison latine - Suárez Martínez, Pedro Manuel (Pallas, 2017)
Together with the regular vocative forms in -ĕ of the Latin second declension like domine, we find the ending -ī in nouns that make their nominative in -ius, like Antonius, Antonī. Research so far has not found a convincing explanation in order to account for other historical oddities, such as the fact that the vocative and genitive of some of those nouns, apparently identical, are pronounced differently : voc. Váleri, gen. Valéri. Our contribution tries to clarify the whole problem by proposing a new hypothesis, which is much simpler than previous ones.